Oral versus Vaginal Misoprostol for Labour Induction : A Comparative Study - Eke P Mahacakri; Â Nuswil Bernolian; Wim T Pangemanan; Theodorus Theodorus (Indonesian Socety of Obstetrics and Gynecology, 2018)
Objective: To compare the efficacy and safety of hourly titrated oralmisoprostol in solution (OMS) with vaginal misoprostol (PV) forlabor induction.Methods: Randomized Controlled Trial (RCT), double blind-add onthe study was conducted from January-November 2016 in deliveryward of Moh. Hoesin general hospital. Women ï‚³30 weeks of gestationwith an unfavorable cervix (Bishop score ï‚£6) and an indicationfor labor induction were randomly assigned to receive titrated oralor vaginal misoprostol. The OMS group received a basal unit of20 ml misoprostol solution (1 ïg/ml) every 1 hour for four dosesand then were titrated against individual uterine response. In theabsence of regular uterine contractions, the dose was increased to40 ml hourly for four doses and then 60 ml for four doses. Thevaginal group received 25 ïg every 4 hours until attaining a morefavorable cervix for three doses. All the subjects received amylumplacebo. In labor within 12 hours was the primary outcome.Results: A total of 30 women were enrolled in this study. One subjectin the OMS group was dropped out due to eclamptic seizure. Theaverage interval from induction until in labour in OMS group was5.75ï‚±3.14 hour and 6.60ï‚±4.46 hour in PV group (p = 0.56). In labourstage was achieved within 12 hours in 14 women (100%) in OMSgroup and 14 women (93.3%) in PV group (p = 1.00). Vaginaldelivery was achieved within 24 hours in 13 women (92.9%) inOMS group and 15 women (100%) in PV group. The incidence ofuterine hyperstimulation/ tachysystolic was 7.1% in OMS groupcompared with 13.3% in PV group. Fetal distress was found only 1case (7.1%) in OMS group. There was no difference in the maternaland neonatal outcome of labor in both the groups.Conclusion: Oral titrated in solution, and vaginal route ofadministration of misoprostol for induction of labour areequally effective and safe.[Indones J Obstet Gynecol 2018; 6-2: 89-97]Keywords: hourly titrated oral misoprostol in solution, oral misoprostol,randomized controlled trial, vaginal misoprostol